The influence of the use of digital technology, market orientation, and entrepreneurial competence on business growth through business adaptability as an intervening variable - Ayu Windari; Suhardi Suhardi; Rahmad Firdaus; Nadia Sri Rejeki; Nur Hidayati (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of digital technology use, market orientation, and entrepreneurial competence on the growth of Micro, Small, and Medium Enterprises (MSMEs) with business adaptability as an intervening variable. The study used a quantitative explanatory approach with data collection through a Likert-scale questionnaire distributed to MSMEs using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to test direct and indirect relationships between variables. The results showed that market orientation and entrepreneurial competence had a positive and significant effect on business adaptability, while the use of digital technology did not show a significant effect. Business adaptability was proven to have a positive and significant effect on MSME business growth. In addition, business adaptability significantly mediated the influence of market orientation and entrepreneurial competence on business growth, but did not mediate the influence of digital technology use. These findings confirm that business adaptability is a key capability in converting internal resources into sustainable business growth. Meanwhile, digital technology only provides optimal impact when strategically integrated and accompanied by the adaptive capabilities of business actors.